Statins: Cardiovascular Risk Reduction in Percutaneous Coronary Intervention—Basic and Clinical Evidence of Hyperacute Use of Statins - Enrique C. Morales-Villegas; Germano Di Sciascio; Carlo Briguori (International Journal of Hypertension)
Reduction of LDL-cholesterol concentration in serum, blocking the isoprenylation of GTPases and the activation of myocyte-protective enzyme systems are three mechanisms that currently explain the lipid and non-lipid effects of statins. However, the decrease of LDL-cholesterol, the reduction of inflammation biomarkers and even the atheroregresion, as surrogate effects to the mechanisms of action of statins would be irrelevant if not accompanied by a significant decrease in the incidence of cardiovascular events. Statins like no other pharmacological group have proven to reduce the incidence of cardiovascular events and prolong life in any clinical scenario. This article review the basic and clinical evidence that support a new indication for HMG-CoA reductase inhibitors “pharmacological myocardial preconditioning before anticipated ischemia” or hyperacute use of statins in subjects with any coronary syndrome eligible for elective, semi-urgent or primary percutaneous coronary intervention: ARMYDA-Original, NAPLES I-II, ARMYDA-ACS, ARMYDA-RECAPTURE, Non-STEMI-Korean, Korean-STEMI trials.